2017
DOI: 10.1136/jmedgenet-2017-104514
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in TDRD9 causes non-obstructive azoospermia in infertile men

Abstract: This is the first report of a recessive deleterious mutation in in humans. The clinical phenotype recapitulates that observed in the knockout mice where this gene was demonstrated to participate in long interspersed element-1 retrotransposon silencing. If this function is preserved in human, our data underscore the importance of maintaining DNA stability in the human male germ line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(60 citation statements)
references
References 39 publications
1
56
0
3
Order By: Relevance
“…Two separate studies in the population of Iran and China reported a significant relationship between HIWI2 gene rs508485 polymorphism and increased risk of spermatogenesis defects [33,34]. Arafat et al reported the relationship between the deletion frameshift mutation in TDRD9 and NOA [35]. In present study, expression of TDRD9 like TDRD1 showed a significantly decreased in the MA samples compared with OA samples.…”
Section: Discussionsupporting
confidence: 52%
“…Two separate studies in the population of Iran and China reported a significant relationship between HIWI2 gene rs508485 polymorphism and increased risk of spermatogenesis defects [33,34]. Arafat et al reported the relationship between the deletion frameshift mutation in TDRD9 and NOA [35]. In present study, expression of TDRD9 like TDRD1 showed a significantly decreased in the MA samples compared with OA samples.…”
Section: Discussionsupporting
confidence: 52%
“…Azoospermia is the main cause of male infertility. To date, mutations on several genes, including SYCP3 ,5 NR5A1 ,6 TDRD9 ,7 TAF4B and ZMYND15 ,8 TEX11 ,9 10 DMC1 ,11 TDRD7 ,12 MAGEB4 ,13 SYCE1 ,14 SOHLH1 15 and MCM8 ,16 have been identified as the causes of azoospermia. However, the genetic basis of this defect in most infertility cases remains unknown 2–4 12…”
Section: Introductionmentioning
confidence: 99%
“…TDRD9 (tudor domain containing 9) also showed increased interaction between the hubs, in disease states, compared with healthy controls. Expression of this entity has been described in gametogenesis with expression in testis and thyroid (103)(104)(105)(106), its association with immune cells or processes has not previously been reported. Its primary function is in transposon silencing and progression of spermatogenesis (107), through an ATPase activity and interaction with PIWI proteins.…”
Section: Tdrd9mentioning
confidence: 92%